2018
DOI: 10.1016/j.schres.2018.01.018
|View full text |Cite
|
Sign up to set email alerts
|

C4A mRNA expression in PBMCs predicts the presence and severity of delusions in schizophrenia and bipolar disorder with psychosis

Abstract: Altered immune function is an established finding in psychotic disorders such as schizophrenia and bipolar disorder with psychosis, though its role in their development and progression remains to be understood. Evidence suggests altered JAK-STAT1 pathway activity in peripheral blood cells from participants with schizophrenia compared to controls. Activation of this pathway leads to increased expression of complement component 4A (C4A), which has recently been implicated in schizophrenia. Here, we examine mRNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 36 publications
(41 reference statements)
2
22
0
Order By: Relevance
“…C4A gene expression increases compared to naïve controls beginning at the early stage of chronic infection, and while this expression does not change significantly between 14dpi and 28dpi or 28dpi and 56dpi, expression increases by approximately 1.5 fold overall between the early and late chronic stages ( Figure 5A ). This gene is primarily known for activation of the complement pathway along with C3A and C5A ( Liesmaa et al., 2018 ; Melbourne et al., 2018 ; Prasad et al., 2018 ; Ji et al., 2019 ). CTSS is a member of the peptidase C1 family that encodes for cathepsin S which is expressed by neurons in the CNS ( Ji et al., 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…C4A gene expression increases compared to naïve controls beginning at the early stage of chronic infection, and while this expression does not change significantly between 14dpi and 28dpi or 28dpi and 56dpi, expression increases by approximately 1.5 fold overall between the early and late chronic stages ( Figure 5A ). This gene is primarily known for activation of the complement pathway along with C3A and C5A ( Liesmaa et al., 2018 ; Melbourne et al., 2018 ; Prasad et al., 2018 ; Ji et al., 2019 ). CTSS is a member of the peptidase C1 family that encodes for cathepsin S which is expressed by neurons in the CNS ( Ji et al., 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…We found 232 of the 663 significant genes’ p-value equal to zero because of unreasonably large estimated causal effects (>1) and/or very small standard error (<1E-3), which may be caused by un-matched LD matrixed. In contrast, the most significant gene among the 89 gene was C4A (causal effect beta= 0.156±0.0145, p=4.45E-27), an well-established causal gene of schizophrenia in recent years 26 27 . It was also the most significant genes prioritized by the median-based MR method (causal effect beta= 0.14±0.008, p=1.9E-60).…”
Section: Resultsmentioning
confidence: 92%
“…But its estimated effect in bipolar disorder was smaller than that of schizophrenia, 0.048±0.006 vs. -0.16±0.015 respectively. Melbourne et al found C4A mRNA expression in peripheral blood mononuclear cells could predict the presence and severity of delusions in bipolar disorder with psychosis 27 . FADS1 was the third most significant genes according to the ML-based MR, p =8.74E-15.…”
Section: Resultsmentioning
confidence: 99%
“…The discoveries of Sekar et al prompted the determination of C4A mRNA expression in patients with schizophrenia, bipolar disorder with psychosis, and controls [ 38 ]. A positive correlation was found between C4A expression and the positive factor scores from the positive and negative syndrome scale (PANSS).…”
Section: Complement Protein C4mentioning
confidence: 99%
“…The second strongest association was seen for hallucinations. The authors suggested that an elevated C4A expression might contribute to the development of psychosis through excessive pruning [ 38 ]. In addition, an increased C4A RNA expression correlated with poorer episodic memory performance and reduced cortical activity in the middle temporal gyrus upon a visual processing task [ 39 ].…”
Section: Complement Protein C4mentioning
confidence: 99%